Circular edge bow-tie nano antenna for energy harvesting systems / Ahasanul Haque - Ahasanul, Haque (2016)
In recent years, a remarkable progress has been observed in the field of energy harvesting via nano-antenna which seems to be a prominent alternative of fossil fuels as this energy is converted from tera hertz range of infrared region. In this study, a novel nano-antenna is designed in order to convert the high frequency solar energy, thermal energy or earth re-emitted sun’s energy into electricity. The proposed antenna is gold printed on a SiO2 layer, designed as a circular edge bow-tie with a ground plane at the bottom of the substrate. The Lorentz-Drude model is used to analyse the behaviour of gold at the infrared band of frequencies. The proposed antenna is designed by 3D-electromagnetic solver, and analysed for optimization of metal thickness, gap size, and antenna’s geometrical length. Simulations are conducted in order to investigate the behaviour of the antenna illuminated by the circularly polarized plane wave. Also, numerical simulations are studied for improving the harvesting E-field of the antenna within 5 THz - 40 THz frequency range and performance is evaluated with respect to different slots in structural geometry. The proposed antenna offers multiple resonance frequency and better return loss within the frequency bands of 23.2 THz to 27 THz (bandwidth 3.8 THz) and 31 THz to 35.9 THz (bandwidth 4.9 THz). An output electric field of 0.656 V/μm is simulated at 25.3 THz. The best fitted gap size at the feed point is achieved as 50 nm with the substrate thickness of 1.2 μm. This study has forecasted its application in next generation solar energy harvesting round the clock for getting higher efficiency, better performance and prolonged operational life.